Design, synthesis and evaluation against Mycobacterium tuberculosis of azole piperazine derivatives as dicyclotyrosine (cYY) mimics - El-wahab, Hend A.A. Abd; Accietto, Mauro; Marino, Leonardo B. [UNESP]; McLean, Kirsty J.; Levy, Colin W.; Abdel-Rahman, Hamdy M.; El-Gendy, Mahmoud A.; Munro, Andrew W.; Aboraia, Ahmed S.; Simons, Claire (Elsevier, 2018)
Three series of azole piperazine derivatives that mimic dicyclotyrosine (cYY), the natural substrate of the essential Mycobacterium tuberculosis cytochrome P450 CYP121A1, were prepared and evaluated for binding affinity and inhibitory activity (MIC) against M. tuberculosis. Series A replaces one phenol group of cYY with a C3-imidazole moiety, series B includes a keto group on the hydrocarbon chain preceding the series A imidazole, whilst series C explores replacing the keto group of the piperidone ring of cYY with a CH2-imidazole or CH2-triazole moiety to enhance binding interaction with the heme of CYP121A1. The series displayed moderate to weak type II binding affinity for CYP121A1, with the exception of series B 10a, which displayed mixed type I binding. Of the three series, series C imidazole derivatives showed the best, although modest, inhibitory activity against M. tuberculosis (17d MIC = 12.5 μg/mL, 17a 50 μg/mL). Crystal structures were determined for CYP121A1 bound to series A compounds 6a and 6b that show the imidazole groups positioned directly above the haem iron with binding between the haem iron and imidazole nitrogen of both compounds at a distance of 2.2 Å. A model generated from a 1.5 Å crystal structure of CYP121A1 in complex with compound 10a showed different binding modes in agreement with the heterogeneous binding observed. Although the crystal structures of 6a and 6b would indicate binding with CYP121A1, the binding assays themselves did not allow confirmation of CYP121A1 as the target.
Keywords: Binding affinity; CYP121A1; Dicyclotyrosine derivatives; Molecular modeling; Mycobacterium tuberculosis; X-ray crystallography